Holocene dynamics of tree taxa populations in Italy - Magri, Donatella; Agrillo, Emiliano; Di Rita, Federico; Furlanetto, Giulia; Pini, Roberta; Ravazzi, Cesare; Spada, Francesco (Review of Palaeobotany and Palynology, 2014)
The Holocene distribution of nine tree taxa (Picea, Abies, Betula, Fagus, Carpinus betulus, Corylus, deciduous and evergreen Quercus, and Olea) in Italy is visually shown by pollen maps. A hundred pollen sites were selected, percentageswere derived fromthe original pollen counts or digitized frompublished diagrams, and represented on maps in subsequent time windows at 1000-year intervals. The pollen maps depict the Holocene history of Italian forest cover as a complex puzzle influenced by very diverse climate, physiography, edaphic and ecological processes, and a long history of human activity. A reasonably goodmatch between the abundance and distribution of pollen data during the last thousand years and the current tree species distribution in Italy indicates that the Holocene pollen maps may represent a fundamental basis for a better understanding of the modern vegetation patterns, often showing discontinuous ranges and complex distributions. Although clear latitudinal gradientswere not detected, regions characterized by high precipitation values hosted dense forest cover since the Holocene onset, while areas with arid climate experienced a delayed increase in trees and a faster decrease during the last four millennia. Fagus, C. betulus and Picea showdisplacement in their distribution inItaly in the course of theHolocene.Other taxa, likedeciduous and evergreen Quercus, and Betula have always occupied the same locations during the Holocene, but show changes in abundance. Abies had a broken distribution in Italy throughout the postglacial. Its populations are currently found within the regions they occupied at the onset of the Holocene. The importance of considering all the available records in their geographical context to reconstruct complex vegetational patterns is discussed.
Keywords: Database; Holocene; Italy; Pollen map; Woody taxon